The Role Of Strategic Management In Competency-Based Curriculum Development - Ahmad Sa’adi; Ilhamsyah, Rizal (Journal of Education and Learning Sciences, 2024)
This study explores the crucial role of strategic management in developing competency-based curricula (CBC) in educational institutions. CBC emphasizes students’ competency achievement, ensuring alignment with labor market demands and contemporary advancements. The integration of strategic management in curriculum development is essential in planning, executing, and evaluating educational programs to maintain their relevance to both student needs and national education standards. Utilizing a literature review method with a qualitative descriptive approach, this study examines how strategic management influences the design and implementation of CBC. The findings indicate that effective strategic management significantly enhances curriculum quality by considering various factors, including industrial demands, educational policies, and global learning trends. A well-managed competency-based curriculum ensures that students acquire the necessary skills and knowledge to thrive in a rapidly changing professional landscape. The study also highlights challenges in implementing CBC, such as the need for continuous curriculum updates, collaboration between educational institutions and industries, and the integration of digital learning tools. To overcome these challenges, institutions must adopt adaptive and data-driven management strategies. Regular assessments, stakeholder involvement, and the use of technology-driven insights can help optimize curriculum effectiveness and maintain its alignment with evolving industry needs. Strategic management serves as a key driver in the successful development and implementation of CBC. By embracing proactive planning and evaluation, educational institutions can create a dynamic and future-ready learning environment that equips students with the competencies required in the modern workforce